2021
DOI: 10.3390/app11199244
|View full text |Cite
|
Sign up to set email alerts
|

Co(II) Complex of Quercetin–Spectral, Anti-/Pro-Oxidant and Cytotoxic Activity in HaCaT Cell Lines

Abstract: In this study a cobalt(II) complex of quercetin was synthetized in the solid state with the general formula Co(C15H9O7)2∙2H2O. The FT-IR, elemental analysis, and UV/Vis methods were used to study the composition of the complex in a solid state and in a water solution. The anti-/pro-oxidant activity of quercetin and the Co(II) complex was studied by means of spectrophotometric DPPH (2,2-diphenyl-1-picrylhydrazyl), FRAP (ferric reducing antioxidant activity) and Trolox oxidation assays. The cytotoxicity of querc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…However, at 100 µM, free Q exhibited higher antioxidant activity. Previous studies on Q-metal complexes with 2:1 Q-metal ratios suggest that the antioxidant activity of the complex might be metal ion dependent, similar to the lower antioxidant activities for Sb (II) and Tb (III) Q complexes [50,51] and the higher antioxidant activities for Co (II) and Pb (II) Q complexes [52][53][54]. The key difference of our samples from reported studies is the NP formation.…”
Section: Antioxidant Activity Of Qfenpsmentioning
confidence: 61%
“…However, at 100 µM, free Q exhibited higher antioxidant activity. Previous studies on Q-metal complexes with 2:1 Q-metal ratios suggest that the antioxidant activity of the complex might be metal ion dependent, similar to the lower antioxidant activities for Sb (II) and Tb (III) Q complexes [50,51] and the higher antioxidant activities for Co (II) and Pb (II) Q complexes [52][53][54]. The key difference of our samples from reported studies is the NP formation.…”
Section: Antioxidant Activity Of Qfenpsmentioning
confidence: 61%
“…An essential step for the development of cobalt(II)-coordinated assembly is the study of the complex species that quercetin can form with the metal ion. For example, Bukhari et al [ 40 ] proposed a 2:1 (metal: ligand) complex in methanol, while Kalinowska et al [ 41 ] reported a 1:2 (metal: ligand) complex in Tris-HCl at pH 7.4. As the stoichiometry of quercetin complex species strongly depends on the experimental conditions, we decided to study the formation of Co(II)-Que complexes in buffered aqueous solution at pH 7.4 (MOPS 10 mM).…”
Section: Resultsmentioning
confidence: 99%
“…The role of LDs in cancer cells, particularly in relation to chemoresistance and cellular stress responses, is complex. The review by Petan et al (2023) highlights the interplay between lipid droplet metabolism and cancer cell viability, suggesting that dysregulated lipid droplet turnover may present novel therapeutic opportunities [13].…”
Section: Discussionmentioning
confidence: 99%
“…In scientific research, flavonoids, as molecules with pleiotropic activity on cancer cells, are being investigated as potential enhancers of the action of cytostatics [ 12 ]. Due to their very limited bioavailability, researchers are considering various strategies [ 13 ], such as modifying their structure, including the creation of metal complexes, encapsulation into nanoformulations as nanoparticles [ 12 , 14 ], and using them as synergistic or additive substances with conventional cytostatics [ 15 ].…”
Section: Introductionmentioning
confidence: 99%